Спецгрупи НКВС і НКДБ: міфи та реальність - Чайковський, А.С. (Архіви України, 2012)
Висвітлюються питання виникнення, функціонування та результати діяльності спецгруп НКВС і НКДБ у 1944–1953 рр. Акцентується увага на причинах їх появи та фальсифікації проблеми, яка розглядється. Освещаются вопросы возникновения, функционирования и результаты деятельности спецгрупп НКВД и НКГБ в 1944–1953 гг. Акцентируется внимание на причинах их появления, а также фальсификации рассматриваемой проблемы. There is highlighted the establishing, functioning and the results of activity of special groups of Commissariat for International Affairs (NKVD) and National Committee of State Security (NKGB) in 1944–1953. The author stresses on the reasons of their arising and the falsification of the problem, discussed in the article.